Pengaruh Kekuatan Pembuktian Kesaksian yang Berdiri Sendiri Terhadap Putusan Perkara Pidana - Dimas Farhann Danu Pratama (PT Elaborium Elevasi Indonesia, 2023)
According to data from the Central Statistical Agency (2021), although Indonesia's crime rate has declined marginally over the past five years, this figure does not accurately reflect the strength of the country's legal system. There are at least 247,218 cases in 2020 and 239,481 cases in 2021. The existence of a judge's ruling is a crucial component of concluding a criminal case. Although witness testimony can be used as evidence in court, one sort of witness statement, known as